2017
DOI: 10.1073/pnas.1613392114
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial transcription factor KLF2 negatively regulates liver regeneration via induction of activin A

Abstract: Endothelial cells (ECs) not only are important for oxygen delivery but also act as a paracrine source for signals that determine the balance between tissue regeneration and fibrosis. Here we show that genetic inactivation of flow-induced transcription factor Krüppel-like factor 2 (KLF2) in ECs results in reduced liver damage and augmentation of hepatocyte proliferation after chronic liver injury by treatment with carbon tetrachloride (CCl4). Serum levels of GLDH3 and ALT were significantly reduced in CCl4-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
3
28
1
Order By: Relevance
“…Activation of the stroma‐derived factor 1 receptor chemokine (C‐X‐C motif) receptor 7 on liver sinusoidal endothelial cells promotes a proregenerative environment by inducing hepatocyte growth factor and Wnt2 production following injury . On the other hand, activation of the endothelial shear‐stress inducible transcription factor Krüppel‐like factor 2 upon injury inhibits hepatocyte proliferation, in part by promoting activin A production . Therefore, paracrine signaling derived from liver endothelial cells serves as a check‐and‐balance system in regulating injury‐induced hepatocyte proliferation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Activation of the stroma‐derived factor 1 receptor chemokine (C‐X‐C motif) receptor 7 on liver sinusoidal endothelial cells promotes a proregenerative environment by inducing hepatocyte growth factor and Wnt2 production following injury . On the other hand, activation of the endothelial shear‐stress inducible transcription factor Krüppel‐like factor 2 upon injury inhibits hepatocyte proliferation, in part by promoting activin A production . Therefore, paracrine signaling derived from liver endothelial cells serves as a check‐and‐balance system in regulating injury‐induced hepatocyte proliferation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our functional studies also showed that in vivo blockade of endothelial Wnt secretion resulted in a dampening of the proliferative response following injury. Together, our findings are in line with previous reports that have highlighted the importance of endothelial cells as a paracrine signaling center for regulating hepatocyte proliferation following injury . Activation of the stroma‐derived factor 1 receptor chemokine (C‐X‐C motif) receptor 7 on liver sinusoidal endothelial cells promotes a proregenerative environment by inducing hepatocyte growth factor and Wnt2 production following injury .…”
Section: Discussionsupporting
confidence: 92%
“…LSECs secrete Wnt ligands and HGF to support replenishment and functional zonation of hepatocytes under steady state . LSECs also contribute to LR . In mice, partial hepatoctemy (PHx)‐induced LR is accompanied by downregulation of angiopoietin‐2 (Angpt2) and transforming growth factor (TGF)‐β1, and increased secretion of Wnt2a and HGF through the VEGF receptor (VEGFR) 2/inhibitor of differentiation‐1 (Id1) pathway in LSECs, leading to enhanced hepatocyte proliferation on day 2 .…”
mentioning
confidence: 99%
“…(18)(19)(20)(21) LSECs also contribute to LR. (14)(15)(16)(17)(22)(23)(24) In mice, partial hepatoctemy (PHx)-induced LR is accompanied by downregulation of angiopoietin-2 (Angpt2) and transforming growth factor (TGF)-b1, and increased secretion of Wnt2a and HGF through the VEGF receptor (VEGFR) 2/inhibitor of differentiation-1 (Id1) pathway in LSECs, leading to enhanced hepatocyte proliferation on day 2. (19,25) VEGFR2-Id1 signaling and re-expressed Angpt2 also promote LSEC-mediated angiogenesis on day 4 post-PHx to re-establish hepatic circulation.…”
mentioning
confidence: 99%
“…Inhibition of KLF2 expression correlates with increased PH severity in apelin knockout mice exposed to hypoxia (Chandra, Razavi et al, 2011). KLF2 overexpression improves pulmonary haemodynamics in hypoxic rats (Dungey, Deng et al, 2011), but can compromise liver function (Chen, Lu et al, 2014, Manavski, Abel et al, 2017, so other therapeutic approaches need to be identified. microRNAs (miRNAs) are small (~22 nucleotide long) non-coding RNAs that negatively regulate gene expression at the posttranscriptional level (Small & Olson, 2011).…”
Section: Introductionmentioning
confidence: 99%